Relationship of Big Five Personality Traits in Self-Compassion among Young Adults - Sohail, Syeda Fatima; Bukhari, Syeda Razia (Annals of Human and Social Sciences, 2025)
The aim of the current study was to explore the role of big five personality traits (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) with self-compassion among young adults. Individuals need to identify their personality traits to find their purpose in life. It is well known that personality traits predict consequential outcomes. The cross-sectional research design was used in the current study. A proposed sample of 387 (both male and female) of age 18 to 25 belonging to general population of Islamabad and Rawalpindi was selected through purposive sampling. Big five personality (OCEAN) was used to measure the personality traits. Self-compassion scale will be used to measure the self-compassion. The interpretation of the current study findings was done through SPSS utilizing descriptive analysis and correlational analysis. Findings of the current study indicated that people who have positive personality traits like openness to experience, conscientiousness, extraversion and agreeableness is significantly positively correlated (p** < .01) with self-compassion and neuroticism is significantly negatively correlated (p** < .01) with self-compassion among young adults. The sample of the study is limited to only twin cities of Pakistan. So future researchers can replicate this study with a more diverse sample from different cities in Pakistan to obtain more generalizable results.